Carpooling and carsharing for commuting in the Paris region: A comprehensive exploration of the individual and contextual correlates of their uses. (July 2019) - Bulteau, Julie; Feuillet, Thierry; Dantan, Sophie
Highlights: This study focused on the correlates of carpooling and carsharing in the Paris area. Socio-economic, interpersonal and contextual variables were explored among workers. Results highlighted the key role of the entourage in carpooling and carsharing. Mobility management policies within the workplace play a important role. Neighborhood density and deprivation were also associated with the two modes. Abstract: The transport sector and the use of individual cars in particular are sources of negative externalities. Shared mobility could form a solution to this issue. This study contributes to a better understanding of the implementability of such a shared mobility by exploring the potential determinants of the use of carpooling and carsharing for commuting among a comprehensive set of socio-demographic, socio-economic, interpersonal and contextual variables. The analyses are based on a representative sample of 2002 workers living in the Paris region. Fisher's exact and Wilcoxon tests and multivariate logistic models were used to characterize the differences between carpoolers and carsharing users and to identify the correlates of mode use in our sample. We outline that the correlates differ between the two shared modes. Our models first highlight the importance of contextual variables: the use of carpooling mainly concerns people who live in rather deprived neighborhoods, while carsharing is overrepresented in well-to-do and denser neighborhoods. We identify the importance of mobility management policies within the workplace and the positive role of information. Having a carpooling service within the company is positively associated with carpooling for commuting. Regarding carsharing, the awareness of existing services (free-floating and peer-to-peer) is positively associated with carsharing use. Finally, the main originality of this study is the identification of the key role of the entourage (colleagues and/or family members) in both carpooling and carsharing. Public policies should therefore consider these results to exploit several levers to favor the use of shared modes in the Paris region.